Strategy for Improving Graduate Quality Through Vocational Programs: A Case Study at MAN 2 Majalengka - Amalia, Ema; Zulaikha, Siti; Trianung , Teguh (FKIP - Universitas Riau, 2025)
This study aims to examine strategies to improve graduate quality through the vocational program at MAN 2 Majalengka. Using a qualitative approach with a naturalistic inquiry method, the research was conducted at MAN 2 Majalengka, Majalengka Regency, West Java, during the odd semester of the 2024/2025 academic year, from July 2024 to April 2025. Data were collected through observation, interviews, document analysis, and literature review. The findings show the vocational program positively influences students’ work readiness and competitiveness. Planning is conducted systematically and collaboratively, involving the school management team, vocational teachers, and industry partners. The curriculum is developed based on labor market demands and student interests. Implementation includes theoretical and practical learning at school, combined with internships in industry, with active support from teachers and instructors. The program’s success is strengthened by cooperation among the principal, vice principals, vocational teachers, industry partners, and parents. Evaluation is carried out through classroom monitoring, field practice, and feedback from industry partners. The impact is evident in the rising number of graduates continuing higher education or entering the workforce. Several alumni also succeeded in creating self-employment. These results confirm the vocational program bridges education and the labor market, thereby enhancing graduate quality significantly.